Anterior Cruciate Ligament Reconstruction: A Systematic Review and Meta-analysis of Outcomes for Quadriceps Tendon Autograft Versus Bone–Patellar Tendon–Bone and Hamstring-Tendon Autografts. Issue 14 (December 2019) - Mouarbes, Dany; Menetrey, Jacques; Marot, Vincent; Courtot, Louis; Berard, Emilie; Cavaignac, Etienne
Background: Comprehensive studies evaluating quadriceps tendon (QT) autograft for anterior cruciate ligament (ACL) reconstruction are lacking. The optimal choice of graft between bone–patellar tendon–bone (BPTB), hamstring tendon (HT), and QT is still debatable. Hypothesis: The current literature supports the use of QT as a strong autograft with good outcomes when used in ACL reconstruction. Study Design: Meta-analysis; Level of evidence, 2. Methods: A systematic search of the literature was performed in PubMed, MEDLINE, Cochrane, and Ovid databases to identify published articles on clinical studies relevant to ACL reconstruction with QT autograft and studies comparing QT autograft versus BPTB and HT autografts. The results of the eligible studies were analyzed in terms of instrumented laxity measurements, Lachman test, pivot-shift test, Lysholm score, objective and subjective International Knee Documentation committee (IKDC) scores, donor-site pain, and graft failure. Results: Twenty-seven clinical studies including 2856 patients with ACL reconstruction met the inclusion criteria. Comparison of 581 QT versus 514 BPTB autografts showed no significant differences in terms of instrumented mean side-to-side difference ( P = .45), Lachman test ( P = .76), pivot-shift test grade 0 ( P = .23), pivot-shift test grade 0 or 1 ( P = .85), mean Lysholm score ( P = .1), mean subjective IKDC score ( P = .36), or graft failure ( P = .50). However, outcomes in favor of QT were found in terms of less donor-site pain (risk ratio for QT vs BPTB groups, 0.25; 95% CI, 0.18-0.36; P < .00001). Comparison of 181 QT versus 176 HT autografts showed no significant differences in terms of instrumented mean side-to-side difference ( P = .75), Lachman test ( P = .41), pivot-shift test grade 0 ( P = .53), Lysholm score less than 84 ( P = .53), mean subjective IKDC score ( P = .13), donor-site pain ( P = .40), or graft failure ( P = .46). However, outcomes in favor of QT were found in terms of mean Lysholm score (mean difference between QT and HT groups, 3.81; 95% CI, 0.45-7.17; P = .03). Conclusion: QT autograft had comparable clinical and functional outcomes and graft survival rate compared with BPTB and HT autografts. However, QT autograft showed significantly less harvest site pain compared with BPTB autograft and better functional outcome scores compared with HT autograft.